New Insights into The Photoactivity of Shape-Tailored BiVO(4) Semiconductors via Photocatalytic Degradation Reactions and Classical Reduction Processes - Kása, Zsolt (Molecules, 2020)
In the present study, additive-free, pH-driven, hydrothermal crystallization was used to obtain shape-tailored monoclinic BiVO(4) photocatalysts. The as-prepared BiVO(4) products were systematically characterized, uncovering their crystallographic, morphologic and optical properties, while their applicability was verified in the visible light-driven photodegradation of oxalic acid and rhodamine B. Monoclinic clinobisvanite was obtained in most cases, with their band gap values located between 2.1 and 2.4 eV. The morphology varied from large, aggregated crystals, individual microcrystals to hierarchical microstructures. It was found that the degradation efficiency values obtained in the case of oxalic acid were directly related to the presence of (040) crystallographic plane, while the degradation of rhodamine B was partially independent by the presence of this structural feature. The importance of (040) crystallographic plane was also demonstrated via the reduction of Cu(2+) to Cu, by analyzing the Raman spectra of the Cu containing samples, the mean primary crystallite size of Cu and Cu content. Furthermore, the presence of (040) crystallographic plane was directly proportional with the hydrodynamic properties of the powders as well.